2020
DOI: 10.1002/iid3.351
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility between skin and vaginal mucosa in sensitization phase of allergic contact dermatitis in mice

Abstract: Introduction Mechanisms underlying skin sensitization in allergic contact dermatitis have been actively studied using the murine contact hypersensitivity (CHS) model. However, much less is known about sensitization at the vaginal mucosa (VM). Methods We developed a CHS model with VM sensitization and epicutaneous elicitation at the ear. We then examined the proliferation activity of lymphocytes, the frequencies of T cells and the differentiation of hapten‐specific T cells in draining lymph nodes (dLNs) after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…We previously reported that VM sensitization induced less ear swelling and fewer proliferating cells in dLNs than those in skin sensitization using a DNFB‐induced CHS model. 8 Consistent with the previous report, DC migration and recruitment after sensitization were limited in the VM compared with the skin (Figures 1 and 2 ). These observations indicated that sensitization ability in the VM might be lower than in the skin based on mechanism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We previously reported that VM sensitization induced less ear swelling and fewer proliferating cells in dLNs than those in skin sensitization using a DNFB‐induced CHS model. 8 Consistent with the previous report, DC migration and recruitment after sensitization were limited in the VM compared with the skin (Figures 1 and 2 ). These observations indicated that sensitization ability in the VM might be lower than in the skin based on mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with skin, there have been far fewer studies on contact allergy in the mucosae, especially in the vaginal mucosa (VM). We previously reported that in the comparison between skin and VM sensitization with 2,4‑dinitrofluorobenzene (DNFB), that preferentially induce Th1 responses, VM sensitization showed lower CHS including local ear swelling and T‐cell responses in the dLNs 8 . Differential DC status may contribute to differences in CHS responses between skin and VM sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…DNFB-sensitized mice were generated as previously described 29 , 30 . Mice were sensitized by applying 20 µL of 0.3% DNFB (v/v) (Sigma-Aldrich, St. Louis, MO, USA) dissolved in acetone/olive oil (4:1, v/v) (AOO) on the shaved dorsal skin on days 0, 1, and 2.…”
Section: Methodsmentioning
confidence: 99%